KERUSAKAN HUTAN SEBAGAI INSPIRASI DALAM KARYA SENI GRAFIS - FARIZ SYAREZA, Dr. Budiwirman, M.Pd. Yofita sandra, S.Pd., M.Pd. (Universitas Negeri Padang, 2016)
Forest destuction is a complex problem in our life, the writer often hear about the efforts to promote forest conservation,however forest destruction is still happened until now. Thefore, the purpose of this thesis is to create an atmosphre of forest destruction in indonesian into graphic art that is able to give criticism and emphaty toward the people about how the importance of forest conservation. From the abpove explanation, the writers are interested to express it into the form of graphic art by using a printing technique ( intaglio print). The writer create into the medium of paper with displaying object of the fallen trees and tree trunk and also the various object on the destruction of forest by printing technique in dry point. The Creation of an idea to be a work of art, through a lengthy process and through a lot of observations. Of the main ideas or underlying ideas will be developed into ten titles work of Graphic Art, namely: 1)